Struggle For Revenge Of Cataleya's Family In Colombiana (2011) Movie Directed By Olivier Megaton: An Individual Psychological Approach - Wardani, Risa; , Drs. H. Abdillah Nugroho, M. Hum; , Nur Hidayat, S.Pd (2013)
The research is proposed to analyze the struggle for revenge on the major character, Cataleya in Colombiana movie based on an Individual Psychological Approach. This study ia a qualitative study using the movie of Olivier Megaton's Colombiana as the object analysis of the study. There are two kinds of data sources primary and secondary. The primary data are from the author's biography, comment, homepage, and website about the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is as follows: first, in this movie, Olivier Megaton wants to illustrate how tragedy in the past influenced someone attitude, especially in here the victim is a girl with 9 years old. Second, based on individual psychological analysis, Olivier Megaton wants to reflect particularly in human striving for superiority and the creativity of human to support their strives and to conquer their inferior.